2014
DOI: 10.1080/17461391.2014.948076
|View full text |Cite
|
Sign up to set email alerts
|

Does current behaviour predict the course of children's physical fitness?

Abstract: The secular trend of reduced physical fitness (PF) leads to increased health risks. The aim of the present paper is to analyse various current factors that affect health behaviour with respect to the course of PF over 2 years. A path analysis combined with a latent growth curve analysis was based on a study that was conducted between June 2008 and June 2010 with 145 primary German school children (52.1% male, average age at baseline 7.95 years ± 0.95). PF was tested with the German Motor Test 6-18. For the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
2
11
0
1
Order By: Relevance
“…Nevertheless, our results reveal that there seems a gap of strength and endurance capacities of children with migration background compared to their classmates without migration background which might be a potential risk factor for cardiovascular diseases and orthopedic problems later on. Therefore, according to Greier and Richelmann and Augste et al preventive and health promoting measures should be implemented as early as possible, with a special focus on children with migration background. However, to implement effective interventions it seems important to address specific factors influencing physical activity and sedentary behavior among ethnic minority groups living in Europe …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, our results reveal that there seems a gap of strength and endurance capacities of children with migration background compared to their classmates without migration background which might be a potential risk factor for cardiovascular diseases and orthopedic problems later on. Therefore, according to Greier and Richelmann and Augste et al preventive and health promoting measures should be implemented as early as possible, with a special focus on children with migration background. However, to implement effective interventions it seems important to address specific factors influencing physical activity and sedentary behavior among ethnic minority groups living in Europe …”
Section: Discussionmentioning
confidence: 99%
“…14 Migration background was defined as present if they or at least one of their parents were born in a foreign country. 8 In a recent study by Hilpert et al 15 among a cohort of about 1000 German first graders with a median age of 7 years, children with a low socioeconomic status and migration background were more likely to exhibit unfavorable health behavior patterns, higher BMI scores, and poorer physical fitness. In addition, studies reported a significant association between migration background and an elevated media use among children and adolescents.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations